Rare Thyroid Cartilage and Diaphragm Metastases from Lung Cancer Visualized on F-18 FDG-PET/CT Imaging - Özcan Kara, Pelin (Galenos Publishing, 2011)
Positron emission tomography (PET) with F-18 fluorodeoxyglucose (FDG) has evolved as a useful imaging modality in the assessment of a variety of cancers, especially for tumor staging and post treatment monitoring. It provides metabolic information. Although, when used alone, relative lack of anatomic landmarks, is a major limitation of PET imaging, this limitation of PET imaging is overcome by the availability of integrated PET/CT imaging. PET and CT images are acquired in one procedure, yielding fused anatomical and functional data sets. Studies with integrated PET/CT imaging have shown promising results. In this case, we present an interesting integrated PET/CT imaging in a lung cancer patient with rare, diaphragm and thyroid cartilage metastases. Conflict of interest:None declared.